The Complexity of the Intersectionality of Domestic and International Non-Governmental Peacebuilding Organisations in South Sudan - Emmaculate Asige Liaga (African Journal of Political Science)
As peace operations and peacebuilding develop, recent discussions have centred on the growth of peacebuilding literature on inclusivity, bottom-up and local approaches. Given that a substantial number of peacebuilding is conducted by Non-governmental organisations, which occupy a middle level to governments and community levels, the paper unpacks the complexity of the interaction of the international and domestic middle-level organisations. The paper presents a case study of South Sudan’s experience, which proves difficult to operationalize the critical inclusivity debates in their operations. The article argues that although there is more participation of local organizations in peacebuilding, the internal and external organizations are still riddled with complex intersections that still maintain the liberal (international) order of peace constituted by a specific form of external governance.